Detection of Leishmania infantum and Leishmania amazonensis in Bats From Endemic and Non-endemic Areas of São Paulo State, Brazil - de França, Danilo Alves [UNESP]; Zúquete, Sara; Louro, Mariana; Kersul, Maíra Guimarães; Menozzi, Benedito Donizete [UNESP]; Fornazari, Felipe [UNESP]; Santos-Gomes, Gabriela; da Fonseca, Isabel Pereira; Langoni, Helio [UNESP] (Wiley, 2024)
Aims: Leishmaniasis is an endemic disease in several regions of Brazil, a tropical country that presents specific environmental conditions that contribute to the development of phlebotomine vectors. This study aimed to detect Leishmania species in naturally infected bats from 17 municipalities in the São Paulo state. Methods and Results: Spleen and liver samples from 203 bats were analysed by real-time PCR and confirmed by conventional PCR followed by gene sequencing. Leishmania DNA was amplified by real-time PCR in 6.4% of the bats and by conventional PCR followed by sequencing in 3.4% of the bats. Positive samples were characterised and included in GenBank. Leishmania species were confirmed in M. molossus, M. nigricans and E. glaucinus bats. Leishmania (Leishmania) amazonensis and L. infantum (syn. L. chagasi) were identified. This is the first detection of Leishmania spp. in bats in the studied areas. All the positive bats came from urban areas. Insectivorous bats were statistically more positive. There was similarity between our sequences and those of a human isolate and a phlebotomine from the region. Conclusions: This result points to bats as important possible reservoir of Leishmania in Brazil and guides the country's health authorities towards epidemiological surveillance, control and prevention actions in endemic areas.
Keywords: chiroptera; leishmaniasis; molecular surveillance; real-time PCR; reservoir